2002
DOI: 10.1038/sj.bmt.1703655
|View full text |Cite
|
Sign up to set email alerts
|

Full chimerism in nonmyeloablative stem cell transplantation in a β-thalassemia major patient (class 3 Lucarelli)

Abstract: Summary:Bone marrow transplantation is the only therapeutic option that can eliminate thalassemic disease. Early results indicated that children in class 3 Lucarelli had a much worse outcome because of high nonrejection mortality and high rejection rate. We therefore tried to investigate a nonmyeloablative stem cell transplantation (NST) approach for such a disease in order to reduce mortality and rejection. We report here the case of successful NST in a 10-year-old girl who had class 3 Lucarelli ␤-thalassemia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
22
0

Year Published

2003
2003
2013
2013

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 24 publications
(24 citation statements)
references
References 7 publications
2
22
0
Order By: Relevance
“…3 Indeed, we have already reported a successful NST in a class 3 Lucarelli severe thalassemia patient. 4 However, the limited availability of matched sibling donors requires that alternative sources of donors be explored. We, therefore, investigated one approach with haploidentical donor in this group of patients.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…3 Indeed, we have already reported a successful NST in a class 3 Lucarelli severe thalassemia patient. 4 However, the limited availability of matched sibling donors requires that alternative sources of donors be explored. We, therefore, investigated one approach with haploidentical donor in this group of patients.…”
mentioning
confidence: 99%
“…5 The extents of hepatomegaly, portal fibrosis, and iron overload in the liver put her into the class 3 risk category as proposed by Lucarelli et al Our experience with NST in a class 3 Lucarelli severe thalassemia patient in the past suggests that the use of hydroxyurea for immune suppression prior to transplantation may prevent graft rejection and contribute to the success of NST in this group of patients. 4 Therefore, the patient was primed with hydroxyurea 20 mg/kg daily for 6 months prior to NST. The conditioning regimen consisted of busulfan, 2 mg/kg given orally every 12 h for 2 days; fludarabine, 35 mg/m 2 infused daily for 5 days; antilymphocyte globulin (Fresenius, HemoCare s , Germany) 5 mg/kg provided daily for 5 days, and total lymphoid irradiation administered as a single fraction of 500 cGy with shielding of the liver, lung, heart, and ovaries.…”
mentioning
confidence: 99%
“…The patients in risk-class III were given hydroxyurea 20 mg/kg daily for at least 3 months prior to BMT to increase immune suppression in order to prevent graft rejection. 6 Pretransplantation patient characteristics are shown in Table 1.…”
Section: Methodsmentioning
confidence: 99%
“…Owing to its immunosuppressive potency and additional myeloablation, fludarabine has been included into nonmyeloablative conditioning regimen for nonmalignant disease. 2 Slavin et al 3 first reported a successful transplantation from related donor using nonmyeloablative conditioning for thalassemia major, followed by a case report by Hongeng et al, 4 in which a 10-year-old girl who had class 3 thalassemia major was successfully transplanted with graft from sibling donor using nonmyeloablative regimen. However, as to our knowledge, there has been no experience with reducedintensity conditioning in children with thalassemia major undergoing unrelated donor transplantation.…”
mentioning
confidence: 99%